Karakteristik Auditee Sebagai Penentu Opini Audit Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2017 - Ririn Lespitasari; Fatchur Rochman (JAMER : Jurnal Akuntansi Merdeka, 2020)
Abstract— Research objectives are to determine the effect of operating margin ratio to total assets on qualified audit opinions. Secondly, To determine the effect of net profit to sales on qualified audit opinions. Thirth, to determine the effect of current asset to current liabilities on qualified audit opinions. And fourth, to determine the effect of operating margin to total assets, net profit to sales and current asset to current liabilities simultaneously to qualified audit opinions. The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2016 – 2017. This type of research is quantitative research. Data collection techniques use documentation. The analysis technique uses linear regression, t test and F test. The results in this study indicate, there is a positive and significant influence between operating margin to total assets and qualified audit reports on Manufacturing Companies listed on the Indonesia Stock Exchange. Scondly, there is a positive and significant influence between net profit and qualified audit reports on Manufacturing Companies Listed on the Indonesia Stock Exchange. Thirth, there is a positive and significant influence between current asset to current liabilities and qualified audit reports on Manufacturing Companies Listed on the Indonesia Stock Exchange. Fourth, there is a simultaneous effect of operating margin to total assets, net profit and current asset to current liabilities against qualified audit reports on Manufacturing Companies listed on the Indonesia Stock Exchange. Keywords—: operating margin to total assets; net profit; current asset to current liabilities; and qualified audit report.